Rumah Susun Di Pekanbaru Dengan Pendekatan Arsitektur Tropis - Putra, Ade; Amanati, Ratna; Susilawaty, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Times showed population growth of Pekanbaru city with the development of local economic activities rapidly. Regional regulations of Pekanbaru city had been not adhered mainly by local people by building houses in the drainage canal and river border line. It was occurred in Siak river area, the people were living along the bank of the river and became into a densely populated area, seedy and less healthy. Therefore, it is necessary to design a Flats are able to answer the needs of the community in avoiding density, untidiness and maintaining health. Because site is located on the bank, so the design must be able to adapt to nature and local climate and then the design of this Flats using tropical architecture approach according Lippsmeier. Where tropical condition requires special handling in its design, the main effect is from the condition of high temperature and high humidity comfort level such as the level of cool air at home by draft. In realizing the convenience so then in this Flats design uses the concept of Verticl Garden in design. So that, the Flats can be a dwelling or shelter for the residents as well as more well ordered.Key Words : Flats, Tropical Architecture, Vertical Garden.